2015
DOI: 10.1209/0295-5075/111/57005
|View full text |Cite
|
Sign up to set email alerts
|

d -wave bond-order charge excitations in electron-doped cuprates

Abstract: We study charge excitation spectra in the two-dimensional t-J model on a square lattice to explore a charge-order tendency recently found in electron-doped cuprates around the carrier density 0.15. The static susceptibility of dwave charge density, which corresponds to the nematic susceptibility at the momentum transfer q = (0, 0), shows two characteristic peaks at momenta of the form q1 = (q ′ , q ′ ) and q2 = (q, 0). These two peaks originate from the socalled 2kF scattering processes enhanced by the d-wave … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
34
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(42 citation statements)
references
References 45 publications
8
34
0
Order By: Relevance
“…This subleading mode may correspond to the CO features observed in RXS experiments 15 , as was discussed in Ref. 27; see also Sec. III E and Sec.…”
Section: Resultssupporting
confidence: 61%
See 3 more Smart Citations
“…This subleading mode may correspond to the CO features observed in RXS experiments 15 , as was discussed in Ref. 27; see also Sec. III E and Sec.…”
Section: Resultssupporting
confidence: 61%
“…28 by employing a model different from that in Ref. 27. On the other hand, high-energy spectrum revealed a quasi-linear dispersive mode around q = (0, 0) with an energy gap about 300 meV (Ref.…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…showed that the present large-N framework can capture short-range charge order recently observed by resonant x-ray scattering 13,21 and also a mysterious mode around q = (0, 0)…”
Section: Model and Formalismmentioning
confidence: 58%